Mtsitso Wa Wuraru; The Analysis of Chopi People’s Music and Its Relation to Indonesia - I Wayan Sudirana (Institut Seni Indonesia Denpasar, 2021)
Many scholars have suggested that Chopi performance was influenced by Indonesian performance practices because of its similarity to Javanese and Balinese Gamelans (Jones 1964, 6). By using non-musical evidence to support their arguments, some have explored in depth the similarities in the use of the terminology, tuning system, organology and orchestration. Even though they found some striking similarities, the lack of evidence of this issue rendered their arguments inconclusive. Therefore, I am here not to argue against or to agree with these scholars. Instead, I will reexamine their arguments, especially the one by A.M. Jones in his Book “Africa and Indonesia,” and based on my knowledge of Indonesian music and literature review of the music of Chopi people, and hopefully to come to the most coherent conclusion. This paper discusses the historical, cultural, and musical form of the music of the Chopi people of Southern Mozambique. The Chopi has an extraordinary musical culture, which features their large xylophone orchestras. I will examine their xylophone (timbila) in terms of its history, instrumentation, cultural and social context, as well as briefly explore the performance of dance based on literature review. I will analyze a piece from Hugh Tracey’s impressive recording called “Msitso Wa Wuraru,” the third orchestral introduction of the Migodo dance performance, to illustrate the complexity of the playing technique and musical performance. Then, I will compare the xylophone tradition of the Chopi and Indonesian, in order to find the similarities and differences between them.